The influence of public environmental concern on the rural living environment in China - Zhang, Wenguang; Jing, Qinlei; Lu, Ji (Frontiers in Sustainable Food Systems, 2024)
Background Despite China's economic growth, rural living environments have often lagged behind. While public participation is gaining importance in environmental governance, the magnitude and mechanism of its impact remain understudied. Purpose This research investigates the relationship between public environmental concerns and the rural living environment in China and explores how public concerns impact living conditions. Methodology Using panel data from 245 prefecture-level cities (2012–2021), we employed the entropy method to measure rural living environment scores and used fixed-effect models to analyze the relationship between public concern and the living environment. Results The findings demonstrate a positive relationship between strong public environmental concerns and improved rural living environments. Further analysis suggests that local government environmental attention acts as a partial mediator in this relationship. Conclusion This study reveals that public participation can influence government policies, ultimately leading to positive environmental outcomes. Promoting public participation in environmental governance is crucial for improving the rural living environment.